2020
DOI: 10.36618/competitive.v15i2.917
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Model Bisnis Halal Logistik Transportasi Berbasiskan Business Model Canvass (BMC)

Abstract: The basic concept of general logistics and halal logistics are actually the same, the difference is that halal logistics is carried out by ensuring that processes in the supply chain separate halal cargo from non-halal cargo. This needs to be done to avoid cross-contamination and ensure that as long as the logistics system of the product is guaranteed halal, therefore halal logistics can be expressed as the application of the halal concept throughout the supply chain activities of suppliers, manufacturing, war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…A survey by Ashari (2021) revealed that the most critical aspect of the halal logistics system is the integrity of halal products, which is focused on preventing contamination of non-halal products with knowledge management and blockchain technology innovation. Efforts to develop a halal logistics implementation model are carried out (Dwiputranti, 2020) with the Business Model Canvas (BMC) approach. It is known that four elements can be applied at PT Iron Bird, namely: Customer, Value Propositions, Resources, and financials.…”
Section: Literature Review Previous Studiesmentioning
confidence: 99%
“…A survey by Ashari (2021) revealed that the most critical aspect of the halal logistics system is the integrity of halal products, which is focused on preventing contamination of non-halal products with knowledge management and blockchain technology innovation. Efforts to develop a halal logistics implementation model are carried out (Dwiputranti, 2020) with the Business Model Canvas (BMC) approach. It is known that four elements can be applied at PT Iron Bird, namely: Customer, Value Propositions, Resources, and financials.…”
Section: Literature Review Previous Studiesmentioning
confidence: 99%
“…Masa tahap pertama akan kewajiban sertifikasi halal akan berakhir pada tanggal 17 Oktober 2024. Oleh karena itu, proses sertifikasi halal terhadap produk UMKM perlu segera dilaksanakan, termasuk UMKM yang berbasis komoditas pertanian (Dwiputranti, 2020). Namun ada beberapa kendala dalam proses percepatan sertifikasi halal ini, di antaranya keterbatasan pengetahuan dan informasi, keterbatasan pemanfaatan teknologi, serta tidak tersedianya dokumen legal untuk kepengurusan administrasi.…”
Section: Pendahuluanunclassified